2013
DOI: 10.1021/ml400260b
|View full text |Cite
|
Sign up to set email alerts
|

Design and Discovery of 2-Arylquinazolin-4-ones as Potent and Selective Inhibitors of Tankyrases

Abstract: Tankyrases (TNKSs) are poly(ADP-ribose)polymerases (PARPs) that are overexpressed in several clinical cancers. They regulate elongation of telomeres, regulate the Wnt system, and are essential for the function of the mitotic spindle. A set of 2-arylquinazolin-4-ones has been designed and identified as potent and selective TNKS inhibitors, some being more potent and selective than the lead inhibitor XAV939, with IC 50 = 3 nM vs. TNKS-2. Methyl was preferred at the 8-position and modest bulk at the 4-position of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 33 publications
(57 reference statements)
1
58
0
Order By: Relevance
“…Figure 1 shows the structures of some known inhibitors of the TNKSs. XAV939 1 7 and GM244-LM 2 35 both bind at the nicotinamide-binding site, as do our 2-arylquinazolin-4-ones 3 36,37 and flavones, including 4. 38,39 Our lead water-soluble inhibitor of PARP-1 and PARP-2, 5-AIQ 11a, [40][41][42][43][44] binds only weakly to the TNKSs, with IC 50 in the low lM range (preliminary data not shown).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Figure 1 shows the structures of some known inhibitors of the TNKSs. XAV939 1 7 and GM244-LM 2 35 both bind at the nicotinamide-binding site, as do our 2-arylquinazolin-4-ones 3 36,37 and flavones, including 4. 38,39 Our lead water-soluble inhibitor of PARP-1 and PARP-2, 5-AIQ 11a, [40][41][42][43][44] binds only weakly to the TNKSs, with IC 50 in the low lM range (preliminary data not shown).…”
Section: Introductionmentioning
confidence: 70%
“…The SAR from our preliminary study 36 on the 2-arylquinazolin-4-ones suggested that the lactam H-bonding motif was essential and that a para-substituted benzene ring could be accepted by the hydrophobic cavity. One example, (3: R 4 0 = CH 2 NHCbz, R 8 = Me) projected deep into the tunnel, with only slight loss of activity.…”
Section: Design Of Inhibitorsmentioning
confidence: 97%
See 3 more Smart Citations